ANALISIS TINGKAT LIKUIDITAS PT DIAMOND FOOD INDONESIA Tbk - Zilfana, Zilfana; Sudirman, Hudyah Astuti; Sitorus, Astrid Napita (LPPM University 17 Agustus 1945 Samarinda, 2024)
Liquidity is the company's ability to meet its maturing obligations. Companies are not only responsible for generating profits in their production activities but are also required to be able to fulfill their obligations to make payments when their obligations are due. A company that has a good level of liquidity will certainly run the company well and productively. This research was conducted on PT Diamond Food Indonesia Tbk, which is one of the companies engaged in the industry and distribution of food and beverage products. This study aims to determine the level of liquidity of PT Diamond Food Indonesia Tbk in fulfilling its short-term obligations. This research is in the form of quantitative descriptive. Data collection was carried out by researchers using data from the financial statements of PT Diamond Food Indonesia Tbk for the period 2018-2021 obtained from www.idx.co.id, then analyzed using the liquidity ratio formula, namely the current ratio, quick ratio and cash ratio.The results of the research of PT Diamond Food Indonesia Tbk have a good level of liquidity and have the ability to meet their maturing obligations because the company has a liquidity level above 100% in 2018-2021 based on current ratio analysis, cash ratio and quick ratio. Despite having a good level of liquidity, the company needs to maintain its cash ratio so that the company does not experience difficulties in meeting its current obligations.